Association of Serum Magnesium Levels with Frequency of Acute Exacerbations in Chronic Obstructive Pulmonary Disease: A Prospective Study - Gumus, Aziz; Haziroglu, Muge; Gunes, Yilmaz (Pulmonary Medicine, 2014)
Background. The course of chronic obstructive pulmonary disease (COPD) is accompanied by acute exacerbations. The purpose of this study is to determine the association of serum magnesium level with acute exacerbations in COPD (COPD-AE). Materials and Methods. Eighty-nine patients hospitalized with COPD-AE were included. Hemogram, biochemical tests, and arterial blood gases were analyzed. Pulmonary function tests were performed in the stable period after discharge. Patients were followed up at 3 monthly periods for one year. Results. Mean age of the patients was 70.4±7.8 (range 47–90) years. Mean number of COPD-AE during follow-up was 4.0±3.6 (range 0–15). On Spearman correlation analysis there were significant negative correlations between number of COPD-AE and predicted FEV1% (P=0.001), total protein (P=0.024), globulin (P=0.001), creatinine (P=0.001), and uric acid levels (P=0.036). There were also significant positive correlations between number of COPD-AE and serum magnesium level (P<0.001) and platelet count (P=0.043). According to linear regression analysis predicted FEV1% (P=0.011), serum magnesium (P<0.001), and globulin (P=0.006) levels were independent predictors of number of COPD-AE. Conclusions. In this small prospective observational study we found that serum magnesium level during exacerbation period was the most significant predictor of frequency of COPD-AE.